Applications of student activity problems for some kirkman type problems - Vites Longani (2018)
© 2015 by the Mathematical Association of Thailand. All rights reserved. In this paper we apply the ideas from recent works on Student Activity Problems in proposing a theorem on some Kirkman type problems. That is, we find that for any prime number p ≥ 3 it is possible for a school teacher to take p2school girls on a walk each day of the p+1 days, walking with p rows of p girls each, in such a way that each pair of girls walk together in the same row on exactly one day.